TO THEORY OF NON-LINEAR OSCILLATIONS OF BEAMS WITH ONE FREE RATE - S. V. Bosakov; N. S. Schetjko (Наука и техника)
A conclusion has been made that non-linear dynamics problems can be reduced to solution of Duffing’s equation and the paper contains its theoretical investigations. An accurate solution with reference to a period and amplitudes of free continuous oscillations of a freely-supported beam on the basis of physically non-linear material. An example of calculation is given in the paper.